The moderating role of business strategy on the relationship between corporate social responsibility and companies’ economic performance - Leila Asadi; Seyed Ali Vaez; Alireza Jorjor Zadeh; Ahmad Kaabomeir (کاوش‌های مدیریت بازرگانی, 2022)
Introduction: The existence of different groups of stakeholders and the commitment of companies to their interests has highlighted the role of corporate social responsibility in today's world. Corporate social responsibility is the company's commitment to maximize long-term economic, social and environmental well-being through its performance, policies and resources. It is a valuable and irreplaceable resource that has changed the paradigm of organizational performance. Research has shown that companies' performance is influenced by corporate social responsibility. Due to the effect of different factors on the relationship between corporate social responsibility and company performance, in various studies have aimed at the moderating role of different variables in this relationship. One of the effective variables is business strategy because it represents a unique and fundamental element of a company's identity. Thus, business strategy can potentially affect the relationship between corporate social responsibility and corporate performance.Methodology: In terms of purpose, the present study is an applied type. From the point of view of data collection, it is descriptive, and, in terms of nature, it is based on the post-event approach. It is also quantitative because accounting and capital market information is used for calculating the variables. The data related to 104 companies listed in Tehran Stock Exchange during 2011-2018 have been analyzed. Five years of information is required to calculate some variables; therefore, the data required by the sample companies should be available for a period of 12 years (2007-2018). To test the research hypotheses, the multivariate linear regression model and the panel data method were used as well. A combined index based on accounting variables and the average decimal ranking method are used to determine the value of the economic, ethical and legal dimensions of corporate social responsibility. To measure the economic performance of companies, the indicators of economic value added and market value added have been used. The theoretical business strategy framework of Miles and Snow (1978, 2003) has also been used. It classifies business strategies into prospectors, analyzers and defenders based on a composite measure to proxy for a firm’s business strategy. This composite measure strategy involves six firm attributes including ratio of R&D expenses to sales, ratio of employees to sales, one-year percentage change in total sales, ratio of SG&A expenses to sales, standard deviation of the total number of employees, and net property, plant and equipment scaled by total assets. The effect of strategy has been investigated in from the viewpoints of strategy and strategy type.  Results and Discussion: The first to sixth hypotheses investigate the effects of economic, ethical and legal dimensions of corporate social responsibility on economic performance (i.e., economic value added and market value added).  The positive coefficient of variables indicates that increasing the economic, ethical and legal dimensions of corporate social responsibility increases the companies’ economic performance and the hypotheses are confirmed. The seventh to twelfth hypotheses investigate the moderating effects of the business strategy on the relationship between corporate social responsibility and the economic performance of companies. The moderating effect of the business strategy has been studied in two ways, strategy and strategy type. In both methods, the moderator role of the strategy on the relationship between corporate social responsibility and economic value added is positive and significant, and the hypotheses are confirmed. Also, the impact of strategy on the relationship between the economic and ethical aspects of corporate social responsibility and market value added is positive and significant. But the significance of the legal dimension has not been confirmed. The results indicate that, regardless of the presented method and the corresponding calculations, aggressive strategy has a greater impact on the relationship between corporate social responsibility and the economic performance of companies.Conclusion: Based on the statistical results, the positive effect of economic, ethical and legal dimensions of corporate social responsibility on economic performance is confirmed. The results are in accordance with the instrumental theory in which the purpose of corporate social responsibility is earning profit and acquisition of economic benefits for the shareholders. The stakeholder and legitimacy theories support the research findings too. According to the stakeholder theory, the value of the firm is increased by respecting the rights of all the stakeholders. Therefore, paying attention to their various demands by the management will lead to the survival of the organization. Respecting the social norms and the observance of rules and regulations to confirm the legitimacy by the government and general public can also lead the company to achieve its goals. Firms that follow a prospective strategy compete together to produce products and find new markets. They are always looking for innovation in product and market development. On the other hand, firms following a defensive strategy focus on a limited product market, and their efforts are to increase production efficiency. Taken together, the results suggest that business strategy is an important determinant of corporate social responsibility performance. The performance of defenders is similar to the strategy of cost leadership, and the performance of prospectors is similar to the strategy of differentiation. Hence, prospectors take advantage of corporate social responsibility, as their innovation-oriented strategy, and enjoy the benefits of corporate social responsibility more than other companies.